2016
DOI: 10.1017/cem.2016.8
|View full text |Cite
|
Sign up to set email alerts
|

Potential Candidates for a Structured Canadian ECPR Program for Out-of-Hospital Cardiac Arrest

Abstract: Objective: Extracorporeal cardiopulmonary resuscitation (ECPR), while resource-intensive, may improve outcomes in selected patients with refractory out-of-hospital cardiac arrest (OHCA). We sought to identify patients who fulfilled a set of ECPR criteria in order to estimate: (1) the proportion of patients with refractory cardiac arrest who may have benefited from ECPR; and (2) the outcomes achieved with conventional resuscitation. Methods: We performed a secondary analysis from a 52-month prospective registry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…Thus, seven (58.3%) of the sustained ROSC patients, in addition to the eligible non‐sustained ROSC patients may have benefitted from ECPR. Under our criteria, we hypothesise that 63 of the 68 eligible patients identified could have derived some benefit from ECPR with regard to an increased chance of ROSC and/or neurologically intact survival . In a future prehospital ECPR programme, this could potentially translate to an additional 13 lives saved a year based on the 22% survival rate found by one retrospective review of international ECPR practices in OOHCA patients .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, seven (58.3%) of the sustained ROSC patients, in addition to the eligible non‐sustained ROSC patients may have benefitted from ECPR. Under our criteria, we hypothesise that 63 of the 68 eligible patients identified could have derived some benefit from ECPR with regard to an increased chance of ROSC and/or neurologically intact survival . In a future prehospital ECPR programme, this could potentially translate to an additional 13 lives saved a year based on the 22% survival rate found by one retrospective review of international ECPR practices in OOHCA patients .…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggests that there will likely be sufficient ECPR cases for at least one centre, depending on the criteria chosen. However, this is likely to represent a considerable burden in terms of equipment, logistics and coordination, physical space, blood bank capability, human resources and finances …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Canadian registry on consecutive adults with non-traumatic OHCA showed that the integration of an ECPR program into an existing high-performance system of care might have a significant impact on patients outcome, with 68% of OHCA patients surviving to hospital admission and 42% surviving to hospital discharge [64,65].…”
Section: Systems Of Care For Cardiac Arrest Following Acute Myocardiamentioning
confidence: 99%